Hair Dye poisoning – A rare case Report - Neki, N.S.; Jain, Ankur; Bajaji, Rohit; Jindal, Mohit Manav (Journal of Advances in Internal Medicine, 2015)
Hair dye poisoning is not uncommon but an emerging entity in India with increased morbidity and mortality. The main component of hair dye poisoning is paraphenylenediamine (PPD), which is highly toxic thus making it life threatening. PPD poisoning can result in various toxic effects, multiorgan failure and ultimately death. Clinical suspicion and timely management can improve the outcome. We report a case of 35 year old male presented to hospital within 4 hours of consuming hair dye with complaints of swelling of face and neck, vomiting and difficulty in breathing. He was satisfactorily managed with supportive therapy and endotracheal intubation and discharged without any ill effects. Journal of Advances in Internal Medicine 2014;3(2):72-73